2020
DOI: 10.1016/j.cell.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Deep Mutational Scanning of SARS-CoV-2 Receptor Binding Domain Reveals Constraints on Folding and ACE2 Binding

Abstract: The receptor binding domain (RBD) of the SARS-CoV-2 spike glycoprotein mediates viral attachment to ACE2 receptor and is a major determinant of host range and a dominant target of neutralizing antibodies. Here, we experimentally measure how all amino acid mutations to the RBD affect expression of folded protein and its affinity for ACE2. Most mutations are deleterious for RBD expression and ACE2 binding, and we identify constrained regions on the RBD’s surface that may be desirable targets for vaccines and ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

154
2,053
6
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 1,869 publications
(2,218 citation statements)
references
References 151 publications
154
2,053
6
5
Order By: Relevance
“…Surveillance efforts have led to the identification of a number of S mutants among circulating SARS-CoV-2 isolates. Several naturally occurring RBD mutations were shown to abrogate interactions with known mAbs and to reduce immune sera binding, raising concerns that viral neutralization escape mutants could emerge or be selected under pressure from mAbbased anti-viral treatments (42). To investigate if S2E12-and S2M11-mediated neutralization might be affected by SARS-CoV-2 polymorphism, we tested binding of either mAb to 29 S protein variants (corresponding to mutations detected in circulating SARS-CoV-2 isolates) expressed at the surface of CHO cells.…”
Section: Formulation Of Ultrapotent Neutralizing Ab Cocktails Againstmentioning
confidence: 99%
“…Surveillance efforts have led to the identification of a number of S mutants among circulating SARS-CoV-2 isolates. Several naturally occurring RBD mutations were shown to abrogate interactions with known mAbs and to reduce immune sera binding, raising concerns that viral neutralization escape mutants could emerge or be selected under pressure from mAbbased anti-viral treatments (42). To investigate if S2E12-and S2M11-mediated neutralization might be affected by SARS-CoV-2 polymorphism, we tested binding of either mAb to 29 S protein variants (corresponding to mutations detected in circulating SARS-CoV-2 isolates) expressed at the surface of CHO cells.…”
Section: Formulation Of Ultrapotent Neutralizing Ab Cocktails Againstmentioning
confidence: 99%
“…E) Relative surface binding of 47D11, (F) ACE2, (G) CR3022 and (H) an anti-FLAG antibody to full-length SARS2 spike epitope mutants, determined by fluorescence-activated cell sorting. I) Antibody-mediated neutralization of infection of luciferase-encoding VSV particles pseudotyped with wild-type, V367A or V367F SARS2-S. J) Surface representation of the 47D11 bound SARS2-S RBD coloured according to mean mutation effect on expression (red indicates more constrained)( 45 ). The Fab is shown as a ribbon diagram.…”
Section: Resultsmentioning
confidence: 99%
“…Total cellular expression of mutants was comparable to wildtype spike protein as demonstrated by an antibody targeting the C-terminal appended Flag-tag on the spike proteins (Figure 3H), suggesting that mutations in the RBD hydrophobic core have a detrimental effect on protein folding, compromising the tertiary structure of the RBD. A recent study reported deep mutational scanning of SARS2-S RBD residues, revealing how mutation of each of the RBD residues affects expression of folded protein and its affinity for ACE2( 45 ). When the mean mutation effect on expression was mapped on the 47D11 bound RBD, we observed that the hydrophobic pocket, targeted by 47D11, is highly mutationally constrained (Figure 3J).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ∆NA(RBD) construct, described in Fig 1A and the first results subsection below, used the protein sequence for the receptor binding domain (RBD) of Spike from SARS-CoV-2 (isolate Wuhan-Hu-1, Genbank accession number MN908947, residues 331-531). The nucleotide sequence was codonoptimized as previously described [28]. To facilitate surface expression of RBD, the murine immunoglobulin H chain V-region leader sequence was added to the N-terminus.…”
Section: Plasmidsmentioning
confidence: 99%